Glue, method for preparing glue, and polarizing plate

CN117487479BActive Publication Date: 2026-10-09ANHUI WANWEI ADVANCED FUNCTIONAL MEMBRANE MATERIALS RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311450021.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2026-10-09
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

此外,此胶水制成的偏光片再进行加工时,制备的产品可靠性也较差,影响产品外观及良率

Benefits of technology

[0054] (1) By adding acetoacetyl-modified water-soluble cellulose acetate to the adhesive components, the acetoacetyl groups on the water-soluble cellulose acetate will undergo a cross-linking reaction with the acetoacetyl groups on the polyvinyl alcohol, making the overall properties of the adhesive more stable; at the same time, by utilizing the principle of like dissolves like, the modified water-soluble cellulose acetate in the adhesive can improve the affinity between the adhesive and the protective film, thereby improving the adhesion of the adhesive on the protective film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117487479B_ABST
    Figure CN117487479B_ABST
Patent Text Reader

Abstract

The application discloses a kind of glue, glue preparation method and polarizing sheet, it is related to polarizing sheet technical field, the glue includes deionized water 100 parts, acetyl acetyl modified polyvinyl alcohol powder 2-20 parts, modified water-soluble cellulose acetate 0.6-5 parts, metal ion salt 0.05-1 part, crosslinking agent 0.1-5 parts;Wherein, the acetyl substitution degree of modified water-soluble cellulose acetate is 0-1.25, the acetyl acetyl substitution degree of modified water-soluble cellulose acetate is 0.1-1.35;The sum of acetyl substitution degree and acetyl acetyl substitution degree is 0.45-1.35;After adding acetyl acetyl modified water-soluble cellulose acetate to glue component, acetyl acetyl on water-soluble cellulose acetate will occur crosslinking reaction with acetyl acetyl on polyvinyl alcohol, so that the overall property of glue is more stable;Meanwhile, using similar solubility, water-soluble cellulose acetate in water glue can improve the affinity between glue and protective film, and then improve the adhesive force of glue on protective film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polarizer technology, specifically to an adhesive, an adhesive preparation method, and a polarizer. Background Technology

[0002] Polarizing films are structural components of liquid crystal displays (LCDs). Their function is to allow light to pass through and be blocked, thus enabling the LCD to display images. Current polarizing films use a water-soluble polyvinyl alcohol adhesive to bond an inner protective film to at least one side; the protective film commonly used is a cellulose triacetate film.

[0003] In existing adhesive formulations, the main raw material of most adhesives is polyvinyl alcohol modified with acetyl groups, and the main crosslinking agent is one or more of the following: dialdehyde, hydroxymelamine, etc. It forms a crosslinked structure by reacting with the highly reactive α-H on the acetyl group.

[0004] This adhesive itself has good weather resistance, but after high-temperature and high-humidity aging, the rapid shrinkage of the polarizing film is always accompanied by the separation of the polarizing film from the protective film. Further research revealed that the separation of the polarizing film from the protective film is due to the failure of the adhesion between the adhesive and the protective film. Therefore, polarizers made with this adhesive have poor water resistance, are easily affected by moisture, and have a short shelf life. For example, after aging tests in a high-temperature and high-humidity environment, obvious white edges appear on the edges of the polarizer. In addition, when polarizers made with this adhesive are further processed, the reliability of the products is also poor, affecting the product appearance and yield. Summary of the Invention

[0005] The purpose of this invention is to provide an adhesive, an adhesive preparation method, and a polarizing film; and to solve the following technical problems:

[0006] How to improve the weather resistance of the adhesive used in polarizers.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] In a first aspect, the present invention discloses an adhesive comprising the following components in parts by weight:

[0009] 100 parts deionized water;

[0010] 2-20 parts of acetoacetyl-modified polyvinyl alcohol powder;

[0011] 0.6-5 parts of modified water-soluble cellulose acetate;

[0012] 0.05-1 part of metal ion salt;

[0013] Crosslinking agent 0.1-5 parts.

[0014] In a further embodiment of the present invention: the modified water-soluble cellulose acetate is obtained by acetylation of cellulose acetate, or by simultaneous acetylation and carboxylation of cellulose acetate.

[0015] In a further embodiment of the present invention, the metal ion salt is AlCl3.

[0016] In a further embodiment of the invention, the crosslinking agent is ethylenediamine or other crosslinking agents capable of reacting with acetylacetyl groups.

[0017] Furthermore, the sum of the degree of acetyl substitution and the degree of substitution of acetoacetyl in the modified water-soluble cellulose acetate is 0.45-1.35, wherein the degree of substitution of acetoacetyl is 0.1-1.35 and the degree of acetyl substitution is 0-1.25.

[0018] If the degree of substitution of acetyl acetyl in water-soluble cellulose acetate is less than 0.1, then the degree of substitution of acetyl groups is between 0.35 and 1.25. By changing the substitution of acetyl groups to adjust the water solubility of cellulose acetate, there are fewer cross-linked chemical bonds between the water-soluble cellulose acetate and the acetyl protective film, and the water resistance of the water-soluble adhesive decreases. If the degree of substitution of acetyl acetyl in water-soluble cellulose acetate is greater than 1.35, then the water solubility of water-soluble cellulose acetate is poor. Therefore, the adhesive of the present invention must meet the above ranges simultaneously; otherwise, it is not suitable as an additive to improve the affinity between the water-soluble adhesive and the protective film.

[0019] Meanwhile, the amount of modified water-soluble cellulose acetate added must be 0.6-5 parts. If the amount added is less than 0.6 parts, the effect of improving the affinity between the water-based adhesive and TAC will be poor. If the amount added is more than 5 parts, it will affect the adhesion between the water-based adhesive and the polarizing film.

[0020] In a further embodiment of the present invention, the viscosity of the adhesive is 10-100 cP.

[0021] Secondly, the present invention discloses a method for preparing the adhesive as described above, comprising the following steps:

[0022] S1: At an initial temperature of 20-35℃, acetoacetyl modified polyvinyl alcohol powder and modified water-soluble cellulose acetate are added to deionized water and stirred evenly. The temperature is then raised from the initial temperature to 84-96℃ within 1-5 hours under programmed control. This temperature is maintained and stirred for 1-5 hours to obtain material A.

[0023] S2: After material A has cooled to 25-35℃, add the metal ion salt to material A and stir to obtain material B;

[0024] S3: Add the crosslinking agent to material B and stir to obtain the adhesive.

[0025] In a further embodiment of the present invention: in step S2, the stirring time is 0.5-2 hours; in step S3, the stirring time is 1-4 hours.

[0026] Preferably, in step S1, the initial temperature is 28°C.

[0027] Preferably, in step S1, the temperature is controlled by a program and increases from 28°C to 92°C over 3 hours.

[0028] Preferably, in step S1, the heat preservation and stirring time is 2-4 hours.

[0029] Preferably, in step S3, the stirring time is 2-3 hours.

[0030] Thirdly, the present invention discloses a polarizer comprising a polyvinyl alcohol resin film and an inner protective film, wherein an adhesive layer is formed between the polyvinyl alcohol resin film and the inner protective film by an adhesive, wherein the adhesive is the glue described above; preferably, the inner protective film is a cellulose triacetate film, and the polarizer can be prepared by the following scheme:

[0031] A swelling

[0032] Before dyeing, the unstretched polyvinyl alcohol (PVA) film is immersed in a swelling tank filled with a swelling aqueous solution to remove impurities such as dust or anti-blocking agents accumulated on the surface of the PVA film, causing the PVA film to swell. This process improves stretching efficiency, prevents uneven dyeing, and enhances the physical properties of the polarizing film. The swelling aqueous solution can be any known solution in the field, such as pure water or deionized water alone, or with the addition of small molecule alcohols such as glycerol or iodine salts such as potassium iodide. Adding small molecule alcohols or iodine salts can improve processability while the polymer film swells. The temperature of the aqueous solution in the swelling tank can be 20-40°C, and the residence time can be 40-120 seconds.

[0033] B staining

[0034] The swollen polyvinyl alcohol (PVA) membrane is immersed in the dyeing section. The dyeing step involves immersing the PVA membrane in a dyeing tank filled with a dyeing aqueous solution containing a dichroic substance, such as iodine, to allow the PVA membrane to adsorb the iodine. The dyeing tank contains KI / I2 / H3BO3, with the KI concentration preferably being 0-4%, the I2 concentration preferably being 0-1%, the H3BO3 concentration preferably being 0-2%, the pH preferably being 3-6, the dyeing temperature being 25-38°C, and the residence time being 50-100 seconds.

[0035] C crosslinking

[0036] The dyed polyvinyl alcohol membrane is immersed in the crosslinking section. The crosslinking step is a step in which the dyed polyvinyl alcohol membrane is immersed in the crosslinking aqueous solution in a way that prevents the dyeability of the physically adsorbed iodine molecules from being reduced by the external environment, thereby fixing the adsorbed iodine molecules. The KI concentration in the crosslinking tank is preferably 1.8-5%, the H3BO3 concentration is preferably 3-5%, the pH is preferably 3-6, the temperature is preferably 25-38℃, and the residence time is 20-60 seconds.

[0037] D Extension

[0038] If the crosslinking reaction of iodine, as a dichroic dye, is insufficient, iodine molecules may detach due to a humid and hot environment, thus requiring a sufficient crosslinking reaction. Furthermore, to orient the iodine molecules between polyvinyl alcohol molecules and improve optical properties, stretching can be performed at the maximum stretch ratio during the crosslinking step, but this is not a limitation. In this invention, the stretching step can be performed simultaneously with other processes as described above, or it can be performed separately; the stretching step can be performed at least once, or it can be performed multiple times. In the case of multiple performances, it can be performed separately in any step of the polarizer manufacturing process.

[0039] The stretching tank contains KI / H3BO3. The concentration of H3BO3 in the stretching tank and the stretching temperature are key points. If the concentration of H3BO3 is too high, it is easy to cause film breakage and affect the stability of production. If the stretching temperature is too low, it will lead to a reduction in the upper limit of the stretching ratio, increase manufacturing costs and film thickness. Moreover, according to manufacturing experience, when the stretching temperature is higher, it is beneficial to the optical performance of the product. Therefore, the preferred concentration of KI in the stretching tank is 4-5%, the preferred concentration of H3BO3 is 3-4%, the total stretching ratio is 5-7 times, the preferred stretching temperature is 55-68℃, and the residence time is 60-120 seconds.

[0040] E water wash

[0041] The polyvinyl alcohol membrane, after cross-linking and stretching, is immersed in a washing tank filled with a washing aqueous solution to remove unwanted residues such as boric acid that adhered to the polyvinyl alcohol membrane in steps prior to the washing step. In this invention, the washing aqueous solution can be any known washing aqueous solution in the art, such as water, and may also contain iodides, but is not limited to them. In this invention, the temperature of the washing tank can be 10-60°C, but is not limited thereto, and is preferably 20-50°C.

[0042] F complementary color

[0043] After the extended washing process, the polyvinyl alcohol film can be selected to enter the color adjustment stage, which is called color correction. The color correction step can be a step to stabilize the iodine complex located between molecules in the polyvinyl alcohol film that has physically adsorbed iodine complexes, by orienting it close to the boric acid crosslinking. Alternatively, it can be a step to correct the color of the polyvinyl alcohol film that has not been sufficiently dyed by the iodine complexes in the crosslinking step.

[0044] The aqueous solution used in the color-correcting step can be any aqueous solution known in the art without particular limitation. For example, it may contain water and boron compounds such as boric acid as solvents, and may also contain organic solvents and iodides that can dissolve together with water. The KI in the color-correcting tank is preferably 3-5%, preferably 0-1% H3BO3, the pH is preferably 3-5.5, the temperature is preferably 20-30°C, and the residence time is 20-50 seconds.

[0045] G drying

[0046] In this invention, the drying step of the polarizer manufacturing method involves drying a water-washed polyvinyl alcohol film, further enhancing the orientation of the iodine molecules by utilizing the shrinkage caused by drying, and obtaining a polarizer with excellent optical properties. It should be noted that shrinkage refers to the narrowing of the film's width. As for the drying method, any drying method known in the art can be used without limitation, such as natural drying, air drying, heating drying, far-infrared drying, microwave drying, hot air drying, etc. For example, hot air drying can be performed at 20-100°C for 1-10 minutes. Furthermore, the drying temperature can be lowered to prevent deterioration of the polarizer, but this is not a limitation; preferably, it is below 100°C. Moreover, based on manufacturing experience, the oven temperature here not only affects the moisture content but also further affects its weather resistance. As mentioned above, excessive moisture trapped inside the polarizer can easily cause hydrolysis of boric acid at high temperatures. Therefore, it is preferable to control the moisture content of the polyvinyl alcohol film to 5%-15% by controlling the oven temperature.

[0047] H-fit

[0048] After drying, the polarizing film needs to be laminated with a protective film on one or both sides using a water-based adhesive or a UV-curable adhesive. The adhesive can be applied using methods such as casting, Mayer rod coating, gravure coating, comma coating, doctor blade coating, mold coating, dip coating, and spray coating. In this invention, the water-based adhesive is the glue used in this invention.

[0049] I dry

[0050] After the above-described film lamination is performed, a drying process to remove water contained in the adhesive layer formed by the water-based adhesive is preferably carried out to dry the film laminate. Drying can be performed, for example, by introducing the film laminate into a drying oven. The drying temperature is preferably 30-92°C. Below 30°C, the protective film tends to peel off easily from the polarizing film. In addition, when the drying temperature exceeds 92°C, the polarization performance of the polarizing film may deteriorate under the influence of heat. The drying time can be about 100-1000 seconds, and from a productivity point of view, it is preferably 160-800 seconds, more preferably 200-700 seconds.

[0051] J Heat Treatment

[0052] After the drying process, a heat treatment process can be performed, which involves curing the film at room temperature or slightly above room temperature, for example, around 28-45°C, for approximately 10-500 hours. The heat treatment temperature is usually set below the drying temperature; this process ultimately produces the polarizing film.

[0053] The beneficial effects of this invention are:

[0054] (1) By adding acetoacetyl-modified water-soluble cellulose acetate to the adhesive components, the acetoacetyl groups on the water-soluble cellulose acetate will undergo a cross-linking reaction with the acetoacetyl groups on the polyvinyl alcohol, making the overall properties of the adhesive more stable; at the same time, by utilizing the principle of like dissolves like, the modified water-soluble cellulose acetate in the adhesive can improve the affinity between the adhesive and the protective film, thereby improving the adhesion of the adhesive on the protective film.

[0055] (2) The amount of acetoacetyl-modified water-soluble cellulose acetate used in this invention is 0.6-5 parts, and the sum of the degree of substitution of acetyl groups and acetoacetyl is 0.45-1.35, wherein the degree of substitution of acetoacetyl is 0.1-1.35 and the degree of substitution of acetyl groups is 0-1.25. By controlling the above concentration ratio, the chemical bonds of cross-linking between water-soluble cellulose acetate and the protective film are adjusted, thereby improving the affinity between the adhesive and the protective film, making the adhesion between the water adhesive and the polarizing film stronger, that is, improving the weather resistance of the polarizing film. Attached Figure Description

[0056] Figure 1 This is a schematic diagram of the polarizer cutting method in the polarizer water resistance test method of the present invention. Detailed Implementation

[0057] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0058] Example 1

[0059] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0060] The preparation process is as follows:

[0061] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0062] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0063] Example 2

[0064] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 4 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0065] The preparation process is as follows:

[0066] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0067] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0068] Example 3

[0069] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.8 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0070] The preparation process is as follows:

[0071] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0072] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0073] Example 4

[0074] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.7, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0075] The preparation process is as follows:

[0076] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0077] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0078] Comparative Example 1

[0079] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 0.5 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0080] The preparation process is as follows:

[0081] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0082] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0083] Comparative Example 2

[0084] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 6 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0085] The preparation process is as follows:

[0086] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0087] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0088] Comparative Example 3

[0089] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 1.3 and an acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0090] The preparation process is as follows:

[0091] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0092] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0093] Comparative Example 4

[0094] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0.09, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0095] The preparation process is as follows:

[0096] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0097] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0098] Comparative Example 5

[0099] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 1.1, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0100] The preparation process is as follows:

[0101] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0102] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0103] Comparative Example 6

[0104] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0105] The preparation process is as follows:

[0106] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-modified polyvinyl alcohol to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Then continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0107] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0108] Comparative Example 7

[0109] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with an acetyl substitution degree of 0.5 and an acetoacetyl substitution degree of 0, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0110] The preparation process is as follows:

[0111] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0112] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0113] Comparative Example 8

[0114] An adhesive is made from the following components in parts by weight: 100 parts deionized water, 10 parts acetoacetyl-modified polyvinyl alcohol, 2 parts acetoacetyl-modified water-soluble cellulose acetate with acetyl substitution degree of 0 and acetoacetyl substitution degree of 0.4, 0.1 parts AlCl3, and 3 parts ethylenediamine.

[0115] The preparation process is as follows:

[0116] Add deionized water to a three-necked flask, keep it warm at 28°C and stir until homogeneous. Then add acetyl-acetyl modified polyvinyl alcohol and acetyl-acetyl modified water-soluble cellulose acetate to the three-necked flask. After the addition is complete, control the temperature rise slowly from 28°C to 92°C within 3 hours, and keep it at 92°C and stir for 3 hours. When the temperature drops to 40°C, add AlCl3 and continue stirring for 1.5 hours. Continue stirring and slowly add ethylenediamine. After the addition is complete, continue stirring for 2.5 hours to obtain the glue.

[0117] The polyvinyl alcohol polarizing film is attached to the cellulose triacetate protective film using the prepared glue. The glue forms an adhesive layer, and after drying, the polarizing film is obtained.

[0118] To provide a clear understanding of the composition and proportions of the adhesives in Examples 1-4 and Comparative Examples 1-8, they are listed in Table 1 below:

[0119] Table 1

[0120]

[0121] The properties of the adhesives and polarizers prepared in Examples 1-4 and Comparative Examples 1-8 were tested using the following methods:

[0122] a. Adhesive viscosity test method: The viscosity of the sample was tested using an LVDV-1T rotational viscometer at a temperature of 25±0.1℃.

[0123] b. Polarizing film water resistance test method: A schematic diagram of the polarizing film cutting method is shown below. Figure 1 As shown.

[0124] exist Figure 1 In the diagram, rectangle ABCD is considered as a single polarizer produced by this invention. Sides AB and CD are the operating side and driving side of the production line, respectively. Rectangle EFGH is a sample cut from polarizer ABCD with a length of 10cm and a width of 3cm. The angle between sides HE and DC is 45°.

[0125] Immerse the sample in a 60℃ constant temperature water bath and start the timer. After the timer expires, remove the sample and measure the white edge with a ruler. If the white edge is less than 1mm after 4 hours, it is considered to have good water resistance. If the white edge is greater than 1mm after 1 hour, it is considered to have extremely poor water resistance. If the sample exhibits polyvinyl alcohol shrinkage after removal, it is also considered to have extremely poor water resistance.

[0126] To provide a clear understanding of the test results, the test data for the adhesives and polarizers prepared in Examples 1-4 and Comparative Examples 1-8 are listed in Table 2, as follows:

[0127] Table 2

[0128]

[0129]

[0130] As shown in Table 2, the adhesive of the present invention has a low viscosity and good flow properties, making it suitable for bonding polarizer protective films. At the same time, the water resistance of the polarizer is significantly improved when the adhesive provided by the present invention is used on the polarizer.

[0131] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. An adhesive, characterized in that, It consists of the following components in parts by weight: 100 parts deionized water; 2-20 parts of acetoacetyl-modified polyvinyl alcohol powder; 2-4 parts of modified water-soluble cellulose acetate; 0.05-1 part of metal ion salt; Crosslinking agent 0.1-5 parts; The modified water-soluble cellulose acetate is obtained by acetylation of cellulose acetate; The degree of acetyl substitution of the modified water-soluble cellulose acetate is 0-0.8 and not 0; the degree of acetoacetyl substitution of the modified water-soluble cellulose acetate is 0.4-1.

35. The modified water-soluble cellulose acetate has a acetyl substitution degree of 0.45-1.35 plus an acetoacetyl substitution degree.

2. The adhesive according to claim 1, characterized in that, The viscosity of the adhesive is 10-100 cP.

3. A method for preparing the adhesive according to claim 1 or 2, characterized in that, Includes the following steps: S1: At 20-35℃, add acetoacetyl modified polyvinyl alcohol powder and modified water-soluble cellulose acetate to deionized water and stir evenly. Then, control the temperature rise in a programmed manner, raising it from the initial temperature to 84-96℃ within 1-5 hours, and maintain this temperature while stirring for 1-5 hours to obtain material A. S2: After material A has cooled to 25-35℃, add the metal ion salt to material A and stir to obtain material B; S3: Add the crosslinking agent to material B and stir to obtain the adhesive.

4. The method for preparing the adhesive according to claim 3, characterized in that, In step S2, the stirring time is 0.5-2 hours; in step S3, the stirring time is 1-4 hours.

5. A polarizer, characterized in that, The polarizer comprises a polyvinyl alcohol resin film and an inner protective film, and an adhesive layer is formed between the polyvinyl alcohol resin film and the inner protective film by an adhesive, wherein the adhesive is the glue as described in claim 1 or 2.

6. The polarizer according to claim 5, characterized in that, The inner protective membrane is a cellulose triacetate membrane.

Citation Information

Patent Citations

  • Sheet polarizer and a fabricating method thereof

    CN101813799A

  • Adhesive for polarizing plate, polarizing plate, method for producing same, optical film and image display

    CN1894354A